Perancangan dan Pembuatan Aplikasi Retensi dan Pemusnahan Berkas Rekam Medis Di Rsud Dr. H. Moch. Ansari Saleh Banjarmasin - Mohammad Imam; Sustin Farlinda; Feby Erawantini; Niyatul Muna (Jurnal Infokes, 2021)
One of the hospitals that have carried out retention and destruction activities is Dr. H. Moch. Ansari Saleh Banjarmasin. The retention and destruction of medical records are still done manually. This research’s purpose by design and create a retention and extermination application of medical records file. This type of research uses qualitative research with the development of the waterfall model system. Data collection includes interviews, observation, FGD, and documentation. The results of the study are functional and non-functional system requirements for making retention and destruction applications, based on the results of the FGD to the medical record filling staff and the head of the medical record unit. The results of the requirements that have been obtained are interpreted in the design of systems and software made through flowchart systems, context diagrams, data flow diagrams (DFD), and entity-relationship diagrams (ERD). The implementation process and unit test use the MySQL database and the PHP programming language and the interface design uses the Codeigniter Framework. The application system integration test uses the functional test of the Black Box Test method with a 100% system trial success rate. . The results of this functional test indicate that the retention and destruction applications can be integrated and function properly with innovations in the form of an annual import database feature, a feature for retention and destruction reports, and storage of scanned files in pdf format. The existence of this application can help the implementation of retention and destruction of medical record files at Dr. H. Moch. Ansari Saleh Banjarmasin has become more effective and efficient in terms of time, use value, and data security.